2002
DOI: 10.2307/3071765
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental Convergence of Stream Fish Community Traits along Geomorphic and Hydraulic Gradients

Abstract: Abstract. Community convergence across biogeographically distinct regions suggests the existence of key, repeated, evolutionary mechanisms relating community characteristics to the environment. However, convergence studies at the community level often involve only qualitative comparisons of the environment and may fail to identify which environmental variables drive community structure. We tested the hypothesis that the biological traits of fish communities on two continents (Europe and North America) are simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(173 citation statements)
references
References 45 publications
5
166
1
1
Order By: Relevance
“…The observed relations between the abundance and species richness of fish in the Czarny Dunajec and physical characteristics of the channel probably reflect genuine links between channel morphology, habitat conditions and riverine communities (Lamouroux et al, 2002;Smiley and Dibble, 2005;Dauwalter et al, 2008). This study documented the dependence of the number of fish species and specimens on the variability in water depth (and also in grain size of bed material in the case of fish abundance), while their dependence on an aggregated width of lowflow channels was not confirmed.…”
Section: Relationships Between the Abundance And Diversity Of Fish Anmentioning
confidence: 68%
“…The observed relations between the abundance and species richness of fish in the Czarny Dunajec and physical characteristics of the channel probably reflect genuine links between channel morphology, habitat conditions and riverine communities (Lamouroux et al, 2002;Smiley and Dibble, 2005;Dauwalter et al, 2008). This study documented the dependence of the number of fish species and specimens on the variability in water depth (and also in grain size of bed material in the case of fish abundance), while their dependence on an aggregated width of lowflow channels was not confirmed.…”
Section: Relationships Between the Abundance And Diversity Of Fish Anmentioning
confidence: 68%
“…For example, stream fishes have been linked to hydrologic patterns (Poff and Allan 1995), geomorphic features (Lamouroux et al 2002), and habitat stability (Richards et al 1996). For example, stream fishes have been linked to hydrologic patterns (Poff and Allan 1995), geomorphic features (Lamouroux et al 2002), and habitat stability (Richards et al 1996).…”
Section: Constructing the Land-cover Cascadementioning
confidence: 99%
“…For example, Yu and Peters (1997) found that fish in the Platte River, Nebraska, showed preferences for specific ranges of Fd, with some species found only at localities where Fd ≈ 0, Fd < 0.2, or Fd < 0.3. Lamouroux et al (1999Lamouroux et al ( , 2002 and Lamouroux and Jowett (2005) have demonstrated a strong link between the trait composition of fish assemblages and reach-averaged Froude numbers. This link reflects the general association of low Fd (<0.2) with pool habitats and high Fd (>0.4) with riffle and glide habitats (Jowett 1993).…”
Section: Implications For In-stream Biotamentioning
confidence: 99%